2021
DOI: 10.1039/d1sc01846a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, solution dynamics and chemical vapour deposition of heteroleptic zinc complexes via ethyl and amide zinc thioureides

Abstract: Ethyl and amide zinc thioureides [L1ZnEt]2 (1), [L1*ZnEt]2 (2) and [L1Zn(N(SiMe3)2)]2 (3) have been synthesised from the equimolar reaction of thiourea ligands (HL1 = iPrN(H)CSNMe2 and HL1* = PhN(H)CSNMe2) with diethyl zinc and zinc...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Rather, we would suggest that ligand rearrangement is sufficiently fast at temperatures >258 K, to show an averaged signal for the { t Bu} groups in the 1 H NMR spectra. While we are unable to comment on the precise nature of the ligand rearrangement process, it seems reasonable to assume that a low-energy bond-breaking mechanism, with a calculated Δ G ‡ for the rearrangement process of Δ G ‡ = +46 kJ mol –1 , is most likely, as similar processes have been observed elsewhere …”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Rather, we would suggest that ligand rearrangement is sufficiently fast at temperatures >258 K, to show an averaged signal for the { t Bu} groups in the 1 H NMR spectra. While we are unable to comment on the precise nature of the ligand rearrangement process, it seems reasonable to assume that a low-energy bond-breaking mechanism, with a calculated Δ G ‡ for the rearrangement process of Δ G ‡ = +46 kJ mol –1 , is most likely, as similar processes have been observed elsewhere …”
Section: Resultsmentioning
confidence: 80%
“…While we are unable to comment on the precise nature of the ligand rearrangement process, it seems reasonable to assume that a low-energy bond-breaking mechanism, with a calculated ΔG ‡ for the rearrangement process of ΔG ‡ = +46 kJ mol −1 , 17 is most likely, as similar processes have been observed elsewhere. 34 In the case of the adamantyl derivative, 4, meaningful interpretations of VT NMR data could not be obtained due to the overlapping resonances of the {NMe 2 } moieties and the various {CH} and {CH 2 } resonances associated with the adamantyl group.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[24] A chemical explanation to this lowering effect upon coordination with alkanolamines remains unclear, highlighting the urgent need to ascertain the link between molecular structure and precursor properties [26] to make more informed decisions about ligand choice. [27][28][29] There are few literature reports that attempt to establish this link [30] though Paquet et al [31,32] have recently reported the isolation of a range of MOD complexes synthesized by the reaction of copper(II) formate with various pyridines and primary and secondary amines. This study suggested a link between increased H-bonding between the formate counter ion and the NH group of the ligand (confirmed by single crystal X-ray diffraction (SCXRD)) and rising decomposition temperatures from TGA.…”
Section: Introductionmentioning
confidence: 99%
“…There are few literature reports that attempt to establish this link [ 30 ] though Paquet et al. [ 31,32 ] have recently reported the isolation of a range of MOD complexes synthesized by the reaction of copper(II) formate with various pyridines and primary and secondary amines.…”
Section: Introductionmentioning
confidence: 99%
“…Other desired properties of an MOD ink include clean decomposition to target material without residual contaminants, 14 good solubility and long shelf life. 15 Additional pre-requisites for an MOD ink are highlighted in our recent review.…”
Section: Introductionmentioning
confidence: 99%